SIAM CITRUS MARKETING EFFICIENCY IN JEMBER REGENCY - Julian Adam Rijal (UNEJ e-Proceeding, 2012)
Citrus was could to increase farmer prosperity, to arise regional and national economics. Therefore, it needs research about citrus marketing in Jember Regency. This objective of the study was (1) to identify and analyze channel of siam Citrus marketing in Jember Regency; (2) to identify and analyze citrus marketing efficiency. The study was conducted in selected areas of Umbulsari, Jember Regency, East of Java. The determination of research area was based on purposive sampling method. The method of data analysis used in this study was marketing efficiency analysis. The result of research indicate that (1) There are three category that showing channel of siam citrus marketing, there is : (a) from farmer to PP I (compiler merchant) then to PP II (consignor merchant) last to PBLK ( market), (b) from farmer to PBLK through of PP II, (c) from farmer directlyto PBLK (market). (2) Second (2nd) channel of siam citrus marketing is efficient channel. Others there was still imbalance distribution of marketing margin, profit and marketing cost, as well as the ratio of profit to marketing cost of the market actors.